Unlocking the potential of wild rice to bring missing nutrition to elite grains - Tiozon, Rhowell Jr.N.; Zhang, Changquan; Kim, Sung-Ryul; Liu, Qiaoquan; Fernie, Alisdair R.; Sreenivasulu, Nese (Elsevier, 2025)
The domestication and artificial selection of rice involved profound genetic changes that rendered wild rice more suitable for cultivation and consumption. As a result, rice has been extensively used as a caloric source to address hunger without sufficiently considering its total nutritional value. In this review, we highlight how domestication has altered starch quality and other nutritional traits in rice, including flavonoid, protein, and lipid content, as well as digestibility and texture. Precise genetic alterations through transgenic technologies hold significant promise for the reintroduction of key nutrient biosynthesis genes that have been lost in cultivated rice. Although there is currently little concrete evidence that genome editing has improved wild rice, the de novodomestication of wild rice enables the retention of its multi-nutritional properties while enhancing its agronomic performance and grain quality. We propose that the use of accelerated breeding techniques to introgress beneficial nutritional alleles from wild rice into elite pools could advance efforts to use wild rice to improve human health.